Golf swing analysis - The center of mass as a valuable diagnostic parameter - Kreuzpointner, F.; Eibl, F.; Tusker, F. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: There are several swinging techniques in golf which result in different movement sequences. Weight transfer can therefore be a very useful diagnostic parameter to measure differences between skill levels. Top coaches on the PGA Tour stated that the weight transfer is the most important factor within the golf swing [1]. This indicate a relevance for figuring out parameters which can be used by practitioners. So the objective of this study was to distinguish between experts and intermediate players by the variability of their golf swing. Methods: The sequence of interest (SOI) of the golf swing was from take away to impact. Eight experts (n=4 professionals and n=4 with a HCP of -1.25±1.9) and five intermediate players (HCP = -28.3±15.0) were included. Outcome parameters were the traveled distance of the COP, the period of the SOI and the area of variation of the COP (AOV) around the address position during the SOI. The AOV is calculated as an ellipse. The axes of the ellipse are built by the standard deviation of the COP around the medio lateral axis and the anterior posterior axis during the movement. The analysis took place on a pressure distribution platform (4096 sensors with 300Hz; RSscan International ®). All subjects performed a neutral swing on the platform with a pitching wedge. For group comparison the Mann-Whiney U test was used. For correlation analysis the Spearman-Rho correlation coefficient was calculat-ed. The level for statistical significance was set to p < 0.05. Results: The period of the SOI was statistical significant shorter in the expert group (848.6 ± 208.6 ms) than in the intermediate group (1166.0 ± 176.4 ms) (p<.05). The traveled path of the COP (expert group: 211.2 ± 49.6mm; intermediate group: 227.4 ± 44.0 mm (p = .56)) and the AOV (expert group: 11.9 ± 9.5 cm²; intermediate group: 14.5 ± 6.4 cm² (p = .60)) did not show any statistical significant differences. Correlation analysis showed a statistical significant relationship between the HCP and the period of SOI (r = 0.64, p < .05). There is no correlation between the AOV and the HCP nor for the traveled distance of the COP and the HCP. Discussion: Wrobel et al. 2012 [2] found out in the contrary that stated that good players have a decreased COP displacement in comparison to novice players. The reason why we found no difference was because our subjects were more skillful. The higher the quality of the players is the more complex it is to find differences between the skill level. The data show a shorter period of SOI which claims that this might be a relevant performance parameter for better players.